1988
DOI: 10.3146/i0095-3679-15-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modification of the Plant Canopy Environment on Sclerotinia Blight of Peanut

Abstract: The development of Sclerotinia blight, caused by Sclerotinia minor Jagger under various environmental conditions, was studied in field plots of peanuts (Arachis hypogaea L.). The peanut plant canopy was modified to produce desired environmental parameters. The m&cations included the thinning of canopy foliage to allow air circulation that would decrease canopy humidity and the addition of water-filled troughs under an unthinned canopy &at would increase humidity. Canopy relative humidity and soil moisture unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
(1 reference statement)
1
19
0
Order By: Relevance
“…Plants with open canopies had a warmer and drier microclimate within the plant canopy as a result of more air circulation and light penetration, whereas plants with dense canopies had a cooler and wetter microclimate because ofless air circulation and light penetration. The observations of Sclerotinia blight of peanut over a 16-yr period in the current study agree closely with those of others (3,6,10,14) which collectively provide evidence that plant growth has a primary role in determining the time of disease onset.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Plants with open canopies had a warmer and drier microclimate within the plant canopy as a result of more air circulation and light penetration, whereas plants with dense canopies had a cooler and wetter microclimate because ofless air circulation and light penetration. The observations of Sclerotinia blight of peanut over a 16-yr period in the current study agree closely with those of others (3,6,10,14) which collectively provide evidence that plant growth has a primary role in determining the time of disease onset.…”
Section: Resultssupporting
confidence: 93%
“…New flushes of succulent plant growth at branch tips after irrigation are also a likely source of increased vulnerability to infection by S. minor (2,15). Observations in the current study and those of others (5,6,12) have indicated that mycelia from germinating sclerotia at the soil surface and near plant tissues (branches, pegs, leaves, etc.) were responsible for initiating infections in peanut fields.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Unfortunately, the advisory program often calls for sprays late in the season when applications of chlorothalonil may trigger increases in severity ofSclerotinia blight. A dense peanut canopy has been implicated as a factor favoring Sclerotinia blight (5). However, in peanut plots lacking significant differences in defoliation, plots sprayed more frequently with chlorothalonil still had higher incidence of Sclerotinia blight (11), which suggests a direct role for chlorothalonil in triggering an increased severity of the disease.…”
mentioning
confidence: 98%
“…Okrun 5.2 aA 5.0 aA 5.9 aA 5.9 aA Flavor Runner 458 2.4 bA* 4.1 abAB* 4.9 abAB* 6.3 aB* Southwest Runner 3.5 abA* 2.9 abA* 3.3 bA* 3.5 bA* Tamspan 90 3.2 abA* 2.3 bA* 2.2 cA** 1.9 bA* * Significant at the 0.05 probability level for rate within a cultivar given as an uppercase letters (rows) and among lines for a given seeding rate given by lowercase letter (columns). Significant interaction of year 3 cultivar (p # 0.0001) was obtained (Table 5), which may have been due to the quantitative nature of the disease resistance (Wildman et al, 1992;Wildman et al, 1992) and the large degree environment influences the infection process of S. minor (Dow et al, 1988a;Dow et al, 1988bPhipps, 1995 also seen with disease incidence scoring. consistent with the increased differences between cultivars as spacing increased for disease incidence and disease severity (Table 6).…”
Section: Resultsmentioning
confidence: 93%